2006
DOI: 10.1016/j.jsgi.2005.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chinese Green Tea on Weight, and Hormonal and Biochemical Profiles in Obese Patients With Polycystic Ovary Syndrome—A Randomized Placebo-Controlled Trial

Abstract: Green tea supplementation did not significantly reduce body weight in obese women with PCOS, nor did it alter the glucose or lipid metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
3
10

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(142 citation statements)
references
References 24 publications
4
123
3
10
Order By: Relevance
“…The reduction in BW ranged from 0.7 kg (Auvichayapat et al, 2008) to 3.5 kg (Chantre and Lairon, 2002), and the loss in body fat ranged from 0.7 kg (Nagao et al, 2005) to 1.8 kg (Nagao et al, 2007). The dosage of EGCG used in the aforementioned investigations ranged from 100 mg/d (Nagao et al, 2007) to 540 mg/d (Chan et al, 2006). In the 26 human experiments conducted by Hursel et al (2011) and Phung et al (2010), most of the investigations discovered that tea drinking could reduce BW.…”
Section: Prevention Of Metabolic Syndrome (Mets) and Cardiovascular Dmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction in BW ranged from 0.7 kg (Auvichayapat et al, 2008) to 3.5 kg (Chantre and Lairon, 2002), and the loss in body fat ranged from 0.7 kg (Nagao et al, 2005) to 1.8 kg (Nagao et al, 2007). The dosage of EGCG used in the aforementioned investigations ranged from 100 mg/d (Nagao et al, 2007) to 540 mg/d (Chan et al, 2006). In the 26 human experiments conducted by Hursel et al (2011) and Phung et al (2010), most of the investigations discovered that tea drinking could reduce BW.…”
Section: Prevention Of Metabolic Syndrome (Mets) and Cardiovascular Dmentioning
confidence: 99%
“…The optimal EGCG dose to increase fat oxidation and support a weight management has not yet been established. The dosage of EGCG used in those studies ranged from 100 (Nagao et al, 2007) to 540 mg/d (Chan et al, 2006), while the duration of the studies varied from 1 d (Komatsu, 2003;Bérubé-Parent et al, 2005) to 13 weeks (Kovacs et al, 2004).…”
Section: Prevention Of Metabolic Syndrome (Mets) and Cardiovascular Dmentioning
confidence: 99%
“…azalma olduğu, ancak düşük enerjili diyet alan plasebo grubu ile karşılaştırıldığında vücut ağırlığı ve kompozisyonlarında istatistiksel olarak anlamlı fark olmadığı tespit edilmiştir (57). Polikistik over sendromu olan 34 obez kadın ile yapılan bir çalışmada da, 3 ay sonrasında yeşil çay tüketen grubunun vücut ağırlığında %2.4 oranında azalma olduğu, ancak kontrol grubu ile karşılaştırıldığında bu durumun anlamlı olmadığı saptanmıştır (58). Aşırı kilolu ve meme kanseri olan 39 kadın ile yapılan randomize kontrollü bir çalışmada da, 6 ay sonrasında günde 960ml yeşil çay tüketen bireylerin vücut ağırlığında 1.2kg azalma olduğu, plasebo grubunda ise 0.2kg azalma olduğu, ancak bu farkın istatistiksel olarak anlamlı olmadığı belirlenmiştir (37).…”
Section: Journal Of Contemporaryunclassified
“…Chantre and Lairon (2002) reported a 4.6% weight loss over 12 weeks in an open-label study, 2002), but a placebo-controlled study of green tea extract in subjects with polycystic ovarian disease gave a 2.4% weight loss over 3 months that was not significantly greater than the loss with placebo, and there were no improvements in glucose or lipid metabolism (Chan et al, 2006). Kovacs et al (2004) found that green tea extract was no better than placebo in maintaining a 7.5% weight loss over 13 weeks.…”
Section: Green Tea Extractmentioning
confidence: 99%